Onze anos de vigilância dos teores de flúor nas águas de abastecimento público: Métodos, produtos e importância para a saúde pública - Moimaz, Suzely Adas Saliba [UNESP]; dos Santos, Luis Felipe Pupim [UNESP]; Saliba, Nemre Adas [UNESP]; Saliba, Orlando [UNESP] (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2017)
This study aimed to assay the development process and the characteristics of a program in uninterrupted activity for over 11 years, which monitors fluoride content in public water supplies, emphasizing the methodology used in the research, the services provided to cities and specificities of water distribution networks, the products derived from project implementation, the main results obtained in its course, and its importance in favor of public health. Monitoring is necessary to reach the maximum benefit in the prevention of tooth decay and minimum risk in fluorosis development. To develop the study, documents and reports of the project’s database and the results of water samples were analyzed. A survey of the intellectual productions generated by the project was performed, maps of water distribution networks of 40 cities in the northwest region of São Paulo state included in the project were analyzed, and the research methodology was presented. The activities carried out in the project have been described with details regarding the main methodological aspects, such as the form of establishment of sample collection points, the laboratory methodology used for the analysis of water samples, the extension experience the project offers to all parties involved, the results of 11 years of sample analyses, the benefits generated to health managers and those responsible for water treatment, among other considerations on the cities. The methodology adopted by the project allows identifying areas where the population may be exposed to higher fluoride concentrations. From November 2004 to December 2015, 50.98% of water samples from all cities were within the optimal parameters.
Eleven years of monitoring fluoride content in public water supplies: Methods, products, and importance to public health
Keywords: Fluoridation; Public health surveillance; Research design